Numerical prediction of heat flow through composite with cracks - Tong, Moo Teng (2014)
This research and software application report provides a thorough investigation on whether the use of COMSOL* is able to simulate the practical result of the similar experiment, B336-optical NDT of composite material (F.H FOO, 2012). Furthermore, an insight of real life applications is being studied to broaden the aspects of the report. Nondestructive testing also known as NDT used test methods to examine an object, material or system without impairing its future usefulness. Subsurface defects are detected from various NDT such as shearography or eddy current. Both detect defects in materials through the application of thermal or sound and electrical waves on the test sample. The use of COMSOL is practiced and understood through test examples before the real implementation of the project starts. Each experiment sample has its own specific test objective state through factors that cause results to change. These various factors are the size of the defect which includes the width, height and length, the shape (square, circle, triangle, and rectangle), temperature (353K, 500K, and 1000K), location of the defects (top, middle, and bottom). The combination of thermal stress with temperature difference determines the fracture region. It is found out that the areas surrounding the cracks are 20% larger than that of the actual crack which the resulted a significant agree between the experimental and simulated results, which demonstrate the utility of this methodology in the study of the thermal response in solids. Finally, the numerical prediction of the relationships is concluded and created for the benefits of the project.